Correlated and Coupled Trajectories of Cancer-Related Worries and Depressive Symptoms among Long-Term Cancer Survivors. Issue 2 (2nd April 2016) - Kypriotakis, George; Deimling, Gary T.; Piccinin, Andrea M.; Hofer, Scott M.
Abstract : The quality of life over time of long-term survivors has become an important part of both cancer and aging research. This paper examines individual differences in trajectories of cancer-related worries and depressive symptoms of 179 participants who completed four waves of annual interviews. Cancer-related worries were significantly associated with both initial level and trajectories of depressive symptoms. In a parallel process growth curve model, the initial level of depressive symptoms was significantly correlated with both the initial level and rate of change in cancer-related worry over time. Our findings indicate that cancer survivors are never completely removed from cancer's threats to quality of life, even as they survive into later life. These findings also suggest that older adults face the dual vulnerability of aging with its growing number of comorbidities and related symptoms along with the vulnerability conferred by cancer-related sequelae and the possibility of recurrence or new cancers.